Concerns on the threat of environmental hazards to human and environment in Malaysia: an exploratory analysis - Tengku Ismail, Tengku Hanidza; Juahir, Hafizan; Aris, Ahmad Zaharin (Springer, 2013)
A total of 1224 university students from Universiti Putra Malaysia, Malaysia, were asked to give a quantitative judgment about the threat to human and the environment with possible answers ranging from “no threat at all” (1) to “extreme threat” (7). This study was carried out from December 2007 to February 2008. Results from this study showed that students tend to rank ‘threat ‘as “high” for hazards familiar to them. The mean score for top five hazards were nuclear technology (6.07), global warming (6.04), drugs (5.92), earthquake (5.79), and tsunami (5.78). On the other hand, unfamiliar hazard such as genetic technology (4.74) and handphone (4.41) were perceived as ‘least threatening’. The role of gender, year of study, race, and academic discipline on risk perception were also examined. Results show that gender plays the biggest role in shaping students’ risk opinion. Female students were more concerned about threat of risk than male students. The differences in opinion follow this order: gender > year of study > race > academic discipline.